Female military pentathlon athletes and scientific research - a mini-review - Mainenti, Míriam Raquel Meira; Miarka, Bianca; Loyola, Marcos Vinícius Marques; dos Santos, Lucas Vieira Coelho; de Mello, Danielli Braga; Zanesco, Angelina [UNESP] (FapUNIFESP (SciELO), 2022)
Aim: to compile existing information in the scientific literature on female military pentathlon athletes. Methods: searches were performed on Pubmed/Medline, Scielo, and Scholar Google databases with specific strings in English and Portuguese. Results: military pentathlon is a discipline that comprises five events, namely: rifle shooting, obstacle run, obstacle swimming, throwing, and cross country running. Our search initially identified 275 records, which were reduced to the final list of 14 after the eligibility criteria analysis was performed in two phases: title + abstract reading and full-text reading. The first record was published in 2007 (recent field of study) and most studies were cross-sectional ones (scarcity of experimental studies), investigating outcomes like psychological, anthropometric, biochemical, biomechanics, cardiopulmonary, nutritional, skin temperature, performance, and prevalence of injury. The female military pentathlon athletes present low values of body fat, energy intake, and high weekly training volume, so professionals must be aware to prevent relative energy deficiency in sports (RED-S) syndrome. The obstacle run was the most investigated event, with lower blood lactate and skin temperature for women athletes. It was also observed that anthropometric, muscle power, and cardiopulmonary variables are well correlated with athletic performance and in some studies, these correlations were stronger for female athletes. Conclusion: scientific research with female military pentathlon athletes is still incipient, especially for experimental design researches, which are highly encouraged in future studies.
Keywords: Athletic performance; Military personnel; Sex characteristics; Sports; Sports medicine